Ancient mitochondrial DNA from the middle neolithic necropolis of Obernai extends the genetic influence of the LBK to west of the Rhine. Issue 3 (22nd July 2016) - Rivollat, Maïté; Réveillas, Hélène; Mendisco, Fanny; Pemonge, Marie‐Hélène; Justeau, Pierre; Couture, Christine; Lefranc, Philippe; Féliu, Clément; Deguilloux, Marie‐France
Abstract: Objectives: The arrival of Neolithic farmers in Europe was the source of major cultural and genetic transitions. Neolithic settlers brought a new set of maternal lineages (mitochondrial DNA), recently well‐characterized on the continental road, from the Balkans to West Germany (Rhine River). In the present study, the first mitochondrial DNA data from groups associated with this continental expansion wave located west of the Rhine River has been provided and their genetic affinities with contemporary groups have been discussed. Material and methods: The mitochondrial DNA analysis of 27 human remains originating from Obernai (5, 000–4, 400 cal. BC), a necropolis located in French Alsace Region and attributed to Grossgartach, Planig–Friedberg, and Roessen cultures was conducted. Results and discussion: Among the 27 individuals studied, 15 HVR‐I sequences and 17 mitochondrial haplogroups could be determined. The analysis of the Obernai gene pool clearly confirmed the genetic homogeneity of Linearbandkeramik (LBK) groups on both sides of the Rhine River. Notably, one N1a sequence found in Obernai is shared with LBK farmers from Central Europe, including one individual from the Flomborn site located approximately 200 km north‐east of Obernai. On the whole, data gathered so far showed major genetic influence of the Danubian wave from Transdanubia to Atlantic French Coast, going by Alsace Region. However, the genetic influence of descendants from the Mediterranean Neolithic expansion and the significant hunter‐gatherer admixture detected further west in the Paris Basin were not perceived in the Obernai necropolis. Conclusions: Genetic homogeneity and continuity within LBK groups can be proposed on both sides of the Rhine River for the middle Neolithic groups. Nevertheless, mitochondrial data gathered so far for Neolithic groups from the entire extant French Territory clearly point out the complexity and the variability of Neolithic communities interactions that is worthy of further investigation.